'Dialogue Not Decoration' – Personal Reflections on Professional Identity and Practice in English Teaching. Issue 4 (2nd October 2021) - Tarpey, Paul
ABSTRACT: In this article I reflect on the early formation of my professional identity and practice. I argue that much of my early practice was 'decorative' in that it masked dominant structures and discourses that often limited learning opportunities. I consider how a dialogic approach to school English is important for offering more authentic teaching and learning experiences within present circumstances dominated by a narrow curriculum focus on canonical literature, Standard English grammar and summative assessment. I end by offering an alternative, through examples of reflective and dialogic practice, aimed at providing students with a more authentic and meaningful learning experience.